2018
DOI: 10.11604/pamj.2018.31.71.15400
|View full text |Cite
|
Sign up to set email alerts
|

Acceptabilité du vaccin antivirus du papillome humain: enquête auprès des parents

Abstract: Le but de ce travail est d'évaluer les connaissances des parents des filles en âge de vaccination sur le vaccin anti virus du papillome humain (HPV), leur acceptabilité du vaccin et les facteurs associés au refus. Nous avons mené une enquête auprès des parents de filles âgées de 8 à 15 ans, suivies pour diverses pathologies au service de pédiatrie du CHU Mohamed VI de Marrakech, Maroc, portant sur le profil des parents, leur connaissances sur le cancer du col de l'utérus, l'HPV, et le vaccin anti HPV, l'accept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
0
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 8 publications
0
0
0
2
Order By: Relevance
“…This is can be considered as a remarkable progress if we take into account certain social stereotypes which considers that "the vaccination is a women's affair." On the other hand, in a study conducted in Morocco, parents refusing HPV vaccination were predominantly male [8]. Previous research as well as this present study found that, parental sensitization about cervical cancer and HPV is significantly associated with vaccination adherence [32,33].…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations
“…This is can be considered as a remarkable progress if we take into account certain social stereotypes which considers that "the vaccination is a women's affair." On the other hand, in a study conducted in Morocco, parents refusing HPV vaccination were predominantly male [8]. Previous research as well as this present study found that, parental sensitization about cervical cancer and HPV is significantly associated with vaccination adherence [32,33].…”
Section: Discussionsupporting
confidence: 51%
“…Previous research as well as this present study found that, parental sensitization about cervical cancer and HPV is significantly associated with vaccination adherence [32,33]. In a survey conducted by (Naima Baddouh et al, 2018) the acceptability rate of the vaccine by parents increased from 63% to 82% after having knowledge about cervical cancer and the human papilloma virus [8]. In Kenya, lack of information about the vaccine has been identified as a barrier to vaccination [34].…”
Section: Discussionmentioning
confidence: 47%
See 1 more Smart Citation
“…Il s´agit d´un progrès remarquable si l´on prend en compte certains stéréotypes sociaux qui considèrent que « la vaccination est une affaire de femmes ». Par contre dans une étude menée au Maroc [ 15 ], les parents refusant la vaccination au HPV étaient majoritairement de sexe masculin. Des recherches antérieures ainsi que cette présente étude ont révélé que l´information des parents sur le cancer du col et le VPH est considérablement associée à la vaccination [ 16 , 17 ].…”
Section: Discussionunclassified
“…Dans une enquête menée par Naima Baddouh et al . [ 15 ], le taux d´acceptabilité du vaccin par les parents avait augmenté de 63% à 82% après avoir eu des connaissances sur le cancer du col et le virus du papillome humain. Au Kenya, le manque d´informations sur le vaccin a été identifié comme un obstacle à la vaccination [ 6 ].…”
Section: Discussionunclassified